Public-Private Partnership Investment Principles and Model for Improving the Development of Maritimetary Infrastucture - Rahmah, Mas; Sari, Ratna Wahyu Kartika; Saraswati, Asih; Fatimah, Rahmania (Journal of Infrastructure Policy and Management (JIPM), 2020)
To support Indonesia’s program as the world’s maritime axis, it is necessary to increase maritime investment. Given the limited financial resources of the State Budget (APBN) in financing maritime infrastructure projects, it is essential to look for alternative financing and investment by involving the private sector through a publicprivate partnership scheme. This paper aims to examine studies on public-private partnership principles for development, improvement and modernization of maritime infrastructure. In addition, this paper analyzes an effective and efficient public-private partnership investment model in the context of the development, improvement and modernization of maritime infrastructure.